2021
DOI: 10.1088/1755-1315/635/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the perspectives of replacing the classic energy plants with Jerusalem artichoke and Sweet Sorghum, analyzing the impact on the conservation of ecosystems

Abstract: To accurately predict the impact of various species of plants on environment is a very difficult task, because their characteristics and specificities together with the external conditions of climate and fauna lead to very complicated systems that are difficult to analyze. The paper aims to assess two technical plants that may be used for the production of biofuels, namely Jerusalem artichoke and Sweet sorghum in evaluating fuel production efficiency and the possibility of being regarded as a viable solution f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The experiment concluded that a high species diversity is needed for proper bacterial population stability and metabolic versatility, while the maximum desirable temperature for continuously thermophilic composting is found to be maximum 60 • C. In order to reduce composting time and increase the quality of the compost, the ratio between leaves and straw should be as high as possible, at least 2:1 [33], alternatively the composting process will take longer. The poorly-matured compost has to be applied far in advance of cultivating a crop to allow for supplementary biological activities in the soil [34,35].…”
Section: Main Findings and Concerns Related To Composting Processesmentioning
confidence: 99%
“…The experiment concluded that a high species diversity is needed for proper bacterial population stability and metabolic versatility, while the maximum desirable temperature for continuously thermophilic composting is found to be maximum 60 • C. In order to reduce composting time and increase the quality of the compost, the ratio between leaves and straw should be as high as possible, at least 2:1 [33], alternatively the composting process will take longer. The poorly-matured compost has to be applied far in advance of cultivating a crop to allow for supplementary biological activities in the soil [34,35].…”
Section: Main Findings and Concerns Related To Composting Processesmentioning
confidence: 99%
“…In recent decades, there has been a tendency to exploit biomass sources to replace traditional fossil fuels. Such a material capable of producing large amounts of biomass is the bamboo [1].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass (vegetable material) is a renewable energy source which becomes more competitive compared to traditional energy production sources in terms of system installation expenses and energy production costs [1]. Biomass stores the energy it receives from the Sun using the process called photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is already affecting food security through increasing temperatures, changing precipitation patterns, and increasing the frequency of some extreme events. In the current changing conditions, research is needed on the development of various crops, that are having superior adaptive capacities and are less affected by climate stress (Nenciu, F., et al 2021;Vlăduţ V., et. al.…”
Section: Introductionmentioning
confidence: 99%